Economic cooperation in Latin America, Africa, and Asia; a handbook of documents. - Wionczek, Miguel S. (Cambridge, M.I.T. Press, 1969)
The purpose of this collection of annotated documents related to economic integration movements in the southern hemisphere is twofold: to provide a guide to those in the economically advanced countries who study current developments in economic "peripheries" of the world or participate in policy-making processes affecting these areas; and to offer some help to those experts and policy makers in Latin America, Africa, and Asia who consider regional economic integration a potentially important weapon in the search for accelerated development and industrialization in their respective countries.
Includes bibliographies.
osc 24/10/2018
Loans
Keywords: Treaties; International economic relations